The effect of working capital management on firm ‘s profitability through manufacturing and service sector in Malaysia during period 2007-2016 - Thi, Thuy Trang Nguyen (2018)
The purpose of this study is to examine the effect of working capital management in firms’ profitability. The study is based on the sample of 10 manufacturing firms and 10 service firms listed on Main Board of Bursa Malaysia, covering a span of ten years from 2007 to 2016. A discriminatory panel regression and Pearson Correlation are used to test the study’s hypothesises. The empirical evidence found that there is presence of significant negative relationship between independent variables, which are average collection period, inventory conversion period, average payment period and cash conversion cycles, and its endogenous variable, which is firm’s profitability. The findings also show a significant relationship between control variables including debt ratio, firm size and current ratio, and profitability.